Prevalence of nicotine dependence among university students in Jordan: a cross-sectional study (Epidemiology, Biostatistics, and Public Health, 2022)
Tobacco epidemic is one of the biggest public health threats the world has ever encountered. The objective of this study was to identify the prevalence of nicotine dependence among university students in Jordan and assess factors associated with this dependence. A cross-sectional study using simple random sampling was conducted among university students from 3 public and 3 private universities selected for their convenience from central, middle, and east Jordan via administering a questionnaire between October 2016 and January 2017. The total number of participants was 892. The overall nicotine dependence was 51.2%. Correlates to nicotine dependence were studying at an undergraduate level (OR=3.6; 95% CI: 1.4-8.1); studying humanities (OR=1.73; 95% CI: 1.2-2.1); existing of a smoking family member (OR=1.63; 95% CI: 1.5-1.9); starting smoking before age of 15 years (OR=1.60; 95% CI: 1.2-2.1); water pipe smoking (OR=1.48; 95% CI: 1.1-2.0); and studying at governmental universities (OR=1.36; 95% CI: 1.0-1.8). Several socio-demographic characteristics had an impact on nicotine dependence. Future research is necessary to further improve our understanding of motives for smoking and dependence.